Impact of collection methods on semen quality, fertility, and hatchability in nunukan chickens - Fatmarisch, Novemia; Indana, Khoiru; Manullang, Jusyenti; Raharja, I M.U.; Mbincar, Bryta; Ardhani, Fikri (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
This study aims to evaluate the fertility and hatchability of Nunukan chickens responding to the rooster semen collected using the dorso-abdominal massage method and a collection tube by presenting a teaser. A total of 20 male Nunukan chickens were divided into two treatment groups, in healthy condition, aged 12-36 months, body weight 2.5-3.4 kg, and housed individually (35x45x60 cm3); the semen was collected every three days. Semen characteristics evaluated macroscopically included color, odor, consistency, volume, and pH; microscopically included sperm concentration, mass motility, progressive individual motility, total sperm per ejaculate, viability, abnormality, and sperm quality factor (SQF); furthermore, the artificial insemination technique was used to evaluate the effect of sperm quality on fertility and hatchability. Both methods showed no difference in macroscopic parameters; color, odor, consistency, and pH, and microscopic parameters (p>0.05); concentration, viability, abnormality, mass motility, and progressive individual motility. While semen volume, total sperm per ejaculate, and SQF showed significant differences (p<0.05). However, the fertility and hatchability rates are not significantly different (p>0.05). Despite the high quantitative qualities of rooster semen obtained with collection tubes and female teasers, Nunukan chickens' fertility and hatchability did not differ significantly (p>0.05) from other semen collection methods. Keywords: collection method; fertility; hatchability, semen, quality